Side Effects and Patient Tolerance with the Use of Blood Flow Restriction Training after ACL Reconstruction in Adolescents: A Pilot Study - Jennifer Prue; Dylan P Roman; Nicholas G Giampetruzzi; Arthur Fredericks; Adel Lolic; Allison Crepeau; J. Lee Pace; Adam P Weaver (International Journal of Sports Physical Therapy)
# Background